An uncommon cause of chest pain - penetrating atherosclerotic aortic ulcer - Htoo Kyaw; Sanah Sadiq; Arnab Chowdhury; Rashin Gholamrezaee; Linus Yoe (Greater Baltimore Medical Center, 2016)
Chest pain is a very common symptom and can be of cardiac or non-cardiac origin. It accounts for approximately 5.5 million annual emergency room visits in the United States, according to 2011 CDC data. Penetrating atherosclerotic aortic ulcer (PAU), an uncommon condition, is also a potential cause of chest pain. We here report the case of a 65-year-old woman who presented with atypical chest and back pain. The pain persisted for 4 weeks necessitating two emergency room visits. Initial tests were non-significant including cardiac troponins, an electrocardiogram (EKG), and a chest X-ray on her first visit. Upon her second visit, she underwent a computed tomography angiogram of chest with contrast which revealed a PAU with an intramural hematoma in descending aorta. The PAU was finally diagnosed with an exclusion of other chest pain causes. She was treated non-surgically with a blood pressure control strategy and pain management. After a 2-month period of smoking cessation and following the achievement of a controlled blood pressure, she felt well without chest pain.